Multisectoral actions in primary health care: A realist synthesis of scoping review. - Resham B Khatri; Daniel Erku; Aklilu Endalamaw; Eskinder Wolka; Frehiwot Nigatu; Anteneh Zewdie; Yibeltal Assefa (PLoS ONE)
Background Multisectoral actions (MSAs) on health are key to implementation of primary health care (PHC) and achieving the targets of the Sustainable Development Goal 3. However, there is limited understanding and interpretation of how MSAs on health articulate and mediate health outcomes. This realist review explored how MSAs influence on implementing PHC towards universal health coverage (UHC) in the context of multilevel health systems. Methods We reviewed published evidence that reported the MSAs, PHC and UHC. The keywords used in the search strategy were built on these three key concepts. We employed Pawson and Tilley's realist review approach to synthesize data following Realist and Meta-narrative Evidence Syntheses: Evolving Standards publication standards for realist synthesis. We explained findings using a multilevel lens: MSAs at the strategic level (macro-level), coordination and partnerships at the operational level (meso-level) and MSAs employing to modify behaviours and provide services at the local level (micro-level). Results A total of 40 studies were included in the final review. The analysis identified six themes of MSAs contributing to the implementation of PHC towards UHC. At the macro-level, themes included influence on the policy rules and regulations for governance, and health in all policies for collaborative decision makings. The meso-level themes were spillover effects of the non-health sector, and the role of community health organizations on health. Finally, the micro-level themes were community engagement for health services/activities of health promotion and addressing individuals' social determinants of health. Conclusion Multisectoral actions enable policy and actions of other sectors in health involving multiple stakeholders and processes. Multisectoral actions at the macro-level provide strategic policy directions; and operationalise non-health sector policies to mitigate their spillover effects on health at the meso-level. At micro-level, MSAs support service provision and utilisation, and lifestyle and behaviour modification of people leading to equity and universality of health outcomes. Proper functional institutional mechanisms are warranted at all levels of health systems to implement MSAs on health.